Peutz-Jeghers syndrome: A circumventable emergency - Sourav Choudhury; Anupam Das; Priyankar Misra; Udipta Ray; Sujata Sarangi (Wolters Kluwer Medknow Publications, 2018)
Peutz-Jeghers syndrome (PJS) is characterized by multiple hamartomatous polyps in the gastrointestinal tract and mucocutaneous pigmentation. Here we present, a case of multiple gastrointestinal hamartomatous polyps in a 22-year-old male who had been operated for intestinal obstruction due to ileocolic intussusception. Resection of the affected segment was done with proximal ileostomy and distal mucous fistula formation. Clinicopathological diagnosis of PJS was made. Later, during ileostomy closure, it was found that the patient had a transverse colonic mass which was resected. Histological examination with immunohistochemistry confirmed it to be a Mucosa-Associated Lymphoid Tissue Lymphoma (MALToma). Colonic MALToma in the background of PJS is a unique case for which it has been reported.